Education, Democracy and Childhood - Catarina Tomás; Elisabete X. Gomes; Carolina Gonçalves; Juliana Gazzinelli (Universidade de Lisboa, 2023)
Building on a dialogue and an opportunity to open the conversation between Educational Theory and Philosophy and Sociology of Childhood, this paper departs from the emerging theories about common/s in education, proposing a new terrain (beyond public and private) where more collective educational experiences may emerge. We aim to contribute to revisit the field of education, democracy, and childhood. Considering Chantal Mouffe's conception of agonistic democracy and Jacques Rancière's plea for its eventful existence, we argue that education must embrace the tensions within democratic experiences, overcoming the modern and rational approaches that underlie its theory and policy. Our argument is strengthened when we bring forth the contribution of Sociology of Childhood to revise conceptions of childhood underneath the established theories of education and democracy. We argue for a view of education as a common good and a commoning experience that enhances children's opportunities to participate in a common world.